Regime shifts in the multi‐annual evolution of a sandy beach profile. Issue 15 (15th August 2018) - Kuriyama, Yoshiaki; Yanagishima, Shinichi
Abstract: Extreme storms occasionally induce extraordinarily large morphological changes, which may have major impacts on coastal resilience, tourism and the environment. Some of the changes are persistent, and they are defined as regime shifts. During a 28‐year period from 1986 to 2014, the foreshore and the inner transition zone of the Hasaki coast of Japan underwent four morphological stages separated by regime shifts in beach profiles. From stage 2 to stages 3 and 4, over a relatively short period between 2006 and 2008, the beach profiles in the foreshore and the inner transition zone drastically changed, mainly because of large offshore waves. From stage 2 to stage 3, the foreshore and the inner transition zone were greatly eroded. Then, from stage 3 to stage 4, although the inner transition zone was further eroded, the foreshore underwent accretion. The severe erosion of the inner transition zone over the 2‐year period formed a steep slope, which was inferred to have led to accretion in the foreshore in stage 4. Stage 4 persisted for approximately 7 years, and the beach profile had not returned to a similar morphology to those of stages 1 or 2 by the end of the study period. © 2018 John Wiley & Sons, Ltd. Abstract : Four morphological stages separated by regime shifts in beach profile evolution were identified on the Hasaki coast, Japan during the 28‐year period from 1986 to 2014. From stage 2 to stage 4, the inner transition zone was heavily eroded, and the foreshore was largely accreted. Stage 4 persisted to the end of the study period, approximately 7 years.